Spectrum allocation, media policy and the key stakeholders' understanding of digitalization in Austria: A shift in the regulatory preferences from broadcasting to broadband. (1st June 2019) - Gadringer, Stefan; Parrilla Guix, Ricard; Trappel, Josef
Recent developments regarding media services transmitted through broadcasting and broadband technology have sparked new trends in digitalization and media convergence. Digitalization was supposed to safeguard the key social role of broadcasting in Europe, but it has mainly intensified its market dependence and orientation. Broadcasters no longer have priority in spectrum policy over online audio‐visual services and broadband. Against this background, we analyse how much broadcasting is losing ground as a privileged cultural form as well as a widely used form of electronic mass communication technology in Austria. Through document analysis and stakeholder interviews, this article addresses how far, between 2007 and 2017, regulation, frequency allocations and the preferences of politicians and key stakeholders point at the substitution of broadcasting by broadband as the main means for the provision of media mass communication. The project draws on a new-institutionalist approach, which states that the output in a given policy process can be understood by researching technological change and the preferences of state and market actors together with the ideological cleavages and the formal and informal institutional rules affecting the process. The research objectives are: (1) to assess the evolution of media policy and communication legislation affecting broadcasting and electronic communication during the final stage of TV digitalization in Austria; (2) to assess the available supply and demand of the radio spectrum for free-to-air (FTA) broadcasting and the frequency share of broadcasters and (mobile) broadband operators; (3) to assess the understanding that political decision-makers and key stakeholders have regarding the role of broadcasting and broadband services both as social practice and as a technological solution for mass communication. The findings, which generally point to a shift from broadcast to broadband, are analysed against the background of the WRC 2015 outcome.